Implementation of Integrative Holistic Early Childhood Development in Kutai Kartanegara Regency, East Kalimantan Province - Heppy Liana; Aslina Yeni; Fajriani Kartika; Utami Dewi (SEAMEO CECCEP, 2024)
Quality Holistic Integrative Early Childhood Development (HI-ECD) is one of the important keys to developing human resources from an early age. The purpose of this research is to find out how the HI-ECD ECD policy is implemented in Kutai Kartanegara District, East Kalimantan Province, Indonesia. In addition, this study also aims to find out the strategies used in the implementation of the policy. This study used descriptive qualitative research methods. The results showed that the Kutai Kartanegara Education Office conducted HI-ECD socialization to 200 ECE managers and teachers. Furthermore, this study found that the HI-ECD policy has been implemented by ECCE managers and teachers in their respective units. Strategies undertaken in implementing HI-ECD include integrated curriculum design and implementation of HI-ECD and parental involvement. However, not all units are implementing these strategies regularly. Collaboration with other government elements has begun. The city government has issued a letter of support for a cooperation agreement for the Community Health Center to support education units by measuring child growth and development and providing healthy food.